Establishing humanitarian lanes during COVID-19 - Cook, Alistair David Blair (2020)
COVID-19 is severely impacting the humanitarian system. It has forced countries to focus on containing the pandemic with national lockdown measures — hindering humanitarian action and denying aid to many affected communities in the Asia Pacific. But countries in the region have begun negotiations to normalise international travel, with Australia and New Zealand being the first to initiate bilateral discussions over the establishment of a ‘Trans-Tasman bubble’ and a ‘humanitarian corridor’ to the Pacific during the pandemic.